Can heat stress affect the psychophysiological responses and locomotor demands of young soccer players during small-sided soccer games? - Ersan Arslan; Yusuf Soylu; Ana Filipa Silva; Osman Yilmaz; Bulent Kilit; Neslihan Akçay; Lukasz Radziminski; Ladislav Batalik (PLoS ONE, 2026)
The study compared the effects of three different heat stress conditions on the psycho-physiological responses and locomotor demands of young players in different small-sided soccer games (SSGs). Sixteen soccer players (age: 16.5 ± 0.5 years) performed 2-a-side and 4-a-side SSGs under three environmental heat stress conditions: low environmental heat (LEH) ≤ 23.9°C, moderate environmental heat (MEH) 24.0–27.9°C, and high environmental heat (HEH) 28.0–32.9°C. Players’ heart rate (HR) responses and total distance covered (TDC) were continuously monitored for all SSGs; the rating of perceived exertion (RPE) and visual analog scale (VAS) were used after each bout. Tympanic temperature (TT) was recorded daily before and after the SSGs. The results demonstrated that for both 2-a-side and 4-a-side SSGs, significant main effects of temperature were observed for HR, %HR max , RPE, and VAS responses (all p < 0.05), indicating progressively increased cardiovascular strain and perceptual load under higher heat stress conditions. In contrast, no significant main effects of temperature were found for TDC and TT responses in either game format. Interaction analyses revealed significant temperature × bout effects for most psychophysiological variables in both SSG formats, including HR, %HR max , RPE, and VAS responses (all p < 0.05), suggesting that responses to heat stress varied across repeated bouts. However, no significant interaction effects were observed for TDC or TT in the 4-a-side SSGs, while only limited interaction effects emerged for TDC in the 2-a-side SSGs format. Overall, the findings indicate that heat stress substantially amplifies cardiovascular and perceptual responses during SSGs, with effects modulated by game format and bout structure. In contrast, TDC and TT appear less sensitive to these conditions. Coaches may use this evidence to manage players’ internal and external load and optimize their team’s performance across various heat-stress conditions.